Capital Management on Profitability: Study of Family Companies in the Food and Beverages Sector Listed on the Stock Exchange Indonesian Effects 2018-2022 - Made Wedaswari; Sari Widati; Maulina Rizky (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
Working capital management is very important for businesses because working capital management includes managing business operational activities. Effective working capital management can increase business profitability. Meanwhile, poor working capital management can lead to lower profitability, even losses. Companies suffering from these losses grow every year. Although it is known that the number of companies listed on the Indonesian Stock Exchange in this sector is increasing every year. Therefore, this research was conducted to detect and find evidence of the impact of working capital management which includes average maturity, inventory conversion period, debt moratorium and cash flow activities on the profitability of family businesses in the food and beverage sector. listed on the stock exchange. Indonesia Stock Exchange for the period 2018 - 2022. The sampling method used was an intentional sampling method obtained from 25 companies with a sample size of 125. The data analysis technique used multiple regression analysis. The research results show that the average delivery time and inventory conversion time have a significant and negative effect on profitability. At that time, the debt moratorium had a positive but insignificant impact on profitability. Meanwhile, operating cash flow has a positive and significant effect on profitability.